Spatio-Temporal Modeling of Land and Pasture Vulnerability in Dairy Basins in Northeastern Brazil - Jéssica Bruna Alves da Silva; Gledson Luiz Pontes de Almeida; Marcos Vinícius da Silva; José Francisco de Oliveira-Júnior; Héliton Pandorfi; Pedro Rogerio Giongo; Gleidiana Amélia Pontes de Almeida Macêdo; Cristiane Guiselini; Gabriel Thales Barboza Marinho; Ivonete Alves Bakke; Maria Beatriz Ferreira (AgriEngineering, 2024)
The objective of this study is to evaluate the spatio-temporal dynamics of land vulnerability and pasture areas in the dairy basins of the states of Pernambuco and Alagoas, which are part of the Ipanema River Watershed (IRW) in the Northeast Region of Brazil. Maps of the Land Use and Land Cover (LULC); the Index of Vulnerability to Degradation (IVD); the Land Vulnerability Index (LVI); time series of Effective Herd (EH), Milked Cows (MC), and Milk Production (MP); and Pasture Cover (PC) and Quality (PCQ) were created as parameters. An opposite pattern was observed between the land use classes of Livestock, Agriculture, and Forest. The IRW area has predominantly flat terrain with a very high risk of degradation. The analysis of MC was consistent with the information from the EH analysis as well as with MP. When assessing Pasture Quality, Severe Degradation areas increased from 2010 to 2014, decreased after 2015, and rose again in 2020. Moderate Degradation areas remained high, while Not Degraded pasture areas were consistently the lowest from 2012 to 2020. Over the 10 years analyzed (2010–2020), the area showed a strong degradation process, with the loss of approximately 16% of the native vegetation of the Caatinga Biome and an increase in pasture areas and land vulnerability.